Behind Closed Doors: Victim Narratives and the Psychological Toll of Childhood Sexual Abuse Survivors - Ali Ijaz; Amna Shafqat; Tayyeba Ahmad; Qamar Usman Pasha (ACADEMIA International Journal for Social Sciences, 2025)
Childhood sexual abuse (CSA) is a deeply distressing experience that leaves lasting psychological and physical effects on survivors. The present qualitative study aimed to explore the lived experiences of females who encountered sexual abuse during childhood, focusing on understanding the characteristics of perpetrators, nature and frequency of abuse, victims’ responses, reporting experiences, family reactions, help-seeking behaviors, and subsequent mental and physical health outcomes. Semi-structured individual interviews were conducted with five female participants from diverse backgrounds, selected through snowball sampling. Open-ended questions were used to elicit rich, descriptive narratives, which were transcribed verbatim and analyzed using content analysis. Findings revealed significant variations in the relationship with the abuser (family member or stranger), type and duration of abuse, and victims’ emotional and psychological reactions. Patterns emerged regarding the role of family responses and the extent to which survivors sought counseling or treatment. To support and validate the findings, three anonymous online narratives of sexual abuse were also analyzed, demonstrating parallel themes. Overall, the study highlights the pervasive emotional impact of childhood sexual abuse and emphasizes the importance of empathetic family responses, accessible psychological support, and increased awareness to facilitate survivors’ recovery.